Experiences of paraprofessionals in US preschool special education and general education classrooms. Issue 1 (23rd December 2014) - Brown, Tiara Saufley; Stanton‐Chapman, Tina L.
Abstract : A substantial challenge confronting public education systems across the world is the employment and retention of high‐quality paraprofessionals (also known as teaching assistants and educational assistants). The current study expands upon previous research by employing a mixed methods design to examine the relationship between paraprofessionals' perceptions of their responsibilities and the corresponding satisfaction and issues relating to their job in the USA. Analytic induction through the generation of themes was used to analyse the qualitative data and revealed that paraprofessionals perceive or demonstrate issues relating to three primary domains: confusion of responsibilities in different contexts, relational power dynamics between paraprofessionals and teachers, and satisfaction based on both monetary compensation and recognition. In addition to the qualitative findings, researchers designed the paraprofessional perception survey, a quantitative survey measuring the concept of paraprofessional perceptions relating to their job. Results from the survey analysis revealed similar findings across domains. Additional results, practice implications and directions for future research are discussed.